Activity Report: Implementation of the CSA Monitoring framework in Doyogena Climate-Smart Landscape, Ethiopia - Ambaw, Gebermedihin; Tadesse, Meron; Recha, John W.M. (2019)
Following up the workshop training held in Doyogena (Ethiopia), the implementation and data collection associated with the climate smart agriculture (CSA) monitoring was carried out between November 2-10, 2019 by a team of 7 enumerators and a supervisor. The main objective of this monitoring was to assess farmers’ adoption/implementation of CSA practices and technologies over the last 12 months and the perceived effects of their implementation on: food security, crops productivity and income, adaptive capacity and gender aspects (labour, participation in decision making, access/control over generated resources). Eleven promising CSA options targeting the rehabilitation of degraded landscapes and ecosystems, and the enhancement of farmer resilience were addressed: Terraces with Desho grass (Pennisetum pedicellatum) a soil and water conservation measure; Controlled grazing; Improved wheat seeds (high yielding, disease resistant & early maturing); Improved bean seeds (high yielding); Improved potato seeds (high yielding, bigger tuber size); Cereal/potato-legume crop rotation (N fixing & non-N fixing); Residue incorporation of wheat or barley; Green manure: vetch and/or lupin during off-season (N fixing in time); Improved breeds for small ruminants; Agroforestry (woody perennials and crops) and Cut and carry for animal feed. The CSA monitoring targeted two persons of opposite sex involved in on-farm activities from a sample of household located in seven villages within the Doyogena Climate-Smart site area. Those included: Tula (01), Suticho (02), Gewada (03), Cholola2 (04), Tachignaw Genjo (05), Duna (06), Gatame 1(07). The households in the first 6 villages were direct beneficiaries of the CCAFS project whereas the ones visited in Gatame1 were non-beneficiaries or “additionals” (potentially non–adopters). Between November 2-10, 2019 a total of 140 households (227 individual farmers: 137 male and 140 females) were surveyed.